Monitoring of 3-D Printing Defects Using the Electromechanical Impedance (EMI) Technique - Soares, Cristiano [UNESP]; Ferreira, Fábio Isaac [UNESP]; de Aguiar, Paulo Roberto [UNESP]; Kennerly, Victória Dutra [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The monitoring of manufacturing processes is essential to ensure the quality and structural integrity of the produced parts. However, several processes still require human intervention for defect detection, such as 3-D printing. This article investigates the potential of a monitoring system based on the electromechanical impedance (EMI) technique to identify defects in 3-D printed parts. A piezoelectric diaphragm was affixed to the print bed, and different printing conditions were used to manufacture the parts. The experimental results demonstrated that the EMI technique can infer defect areas by calculating the root mean square deviation (RMSD) index from the imaginary part of the impedance at a frequency range of (123.5–124.0) kHz. Notably, the diaphragm used in this study was obtained at a cost of less than U.S. ${\$}$ 1, and its performance exhibited a strong correlation. These observations suggest that the proposed system possesses considerable potential for effective monitoring of the 3-D printing process.